Estudo paramétrico sobre superfícies seletivas em frequência reconfiguráveis - Souto, Gabriel Amaral (2020)
The demand for solutions in communication technologies grows as new services and applications emerge. Like any circuit involving electromagnetic signals, telecommunication systems can use active and passive filters to better serve this expanding service. This work presents parametric and operation analyzes of frequency filters as a means of selecting electromagnetic signals, presenting a complete analysis of the design, execution and validation of a Frequency Selective Surfaces (FSS) project used as a filter in communication systems. Through these filtering elements, it is possible to achieve increased directivity of antennas, electromagnetic shielding, beam stirring and beam switching in the active selection of signals and applications in the detection and characterization of materials in any state. When placed under an incident wavefront, thin conducting planar elements that act as an obstacle to an incident wavefront and interact with certain frequencies determined by the designer, in order to reject them or not, so that a service is served. FSS are selective in propagation frequency, incidence angles or even propagation modes. Through the Equivalent Circuit Method, from its primordial elements to its active arrangements, three active band-reject solutions are designed using the short-circuit method; taking the double square loop and double ring model, both with two resonance frequencies, and Jerusalem Cross / Ring, with three resonance frequencies or Tri-band, with FR4 substrate aiming to apply them in Stealth and Beam Switching solutions . Parametric analysis was performed by varying the thickness for all elements of each geometry for the three designs, resulting in variations in the transmission coefficient that form a behavior pattern. The commercial Finite Element Method using the HFSS® (High Frequency Structural Simulator) was used to observe the project's operability in the S band, and later prototypes were built, in switched and non-switched mode, for the three projects, totaling six different prototypes that were measured to search for the transmission coefficient using the Free Space Method through the VNA (Vector Network Analyzer) R & S® 100 kHz / 8.5 GHz. The comparison of the measured and simulated results showed that the project is operational in the design ranges with classic parameters with a transmission coefficient of -17.53 dB, -30.03 dB, -19.06 dB at 1.8 GHz, 3.1 GHz and 5.8 GHz, for the Jerusalem Cross / External Ring project , respectively; -25.03 dB and -27.45 dB for the frequencies of 2.3 GHz and 5.8 GHz, for the double square loop design, respectively and -24.35 dB and -50.01 dB for 2.45 and 5.8 GHz for the 2.45 GHz and 5.8 GHz frequencies for the double circular loop design, respectively